Pengaruh Pelaksanaan Pembelajaran Kurikulum Merdeka Terhadap Minat Belajar PPKn Siswa Kelas IV Sekolah Dasar - Richard D. H. Pangkey; Risal M. Merentek (Peneliti.net, 2023)
The Independent Curriculum is the development of the Independent Curriculum which is expected to be able to restore learning loss conditions in students with learning that is more focused on deepening the material. To realize this goal, the Independent Curriculum has characteristics that are able to provide a learning experience with a pleasant atmosphere. Providing learning with a fun learning atmosphere fosters a higher interest in learning PPKn. This study aims to determine the effect of the implementation of the Independent Curriculum learning on the interest in learning PPKn in class IV SD Gugus Tomohon Selatan. This study uses a quantitative method of typeAfter the fact. The research sample consisted of 133 fourth grade students at SD Gugus Tomohon Selatan. Data is collected through the scale directly. The instruments used include the psychology scale of learning in the Independent Curriculum and interest in learning PPKn. The validity of the instrument was tested based on expert and value validationcorrected item-total correlation. Reliability based on coefficientsAlpha’s Cronbach on the Independent Curriculum scale and interest in learning PPKn shows a value of α = 0.903 and α = 0.934. Research data analysis techniques using a simple linear regression test using the programIBM SPSS Ver 27. The results showed that there was a positive and significant effect of learning the Independent Curriculum on the interest in learning PPKn for fourth grade students at SD Gugus Tomohon Selatan (p<0.05) with a coefficient of determination of 0.490. This can be proven by a simple linear regression equation which is: Y = 18.213 + 0.678X, otherwise H1 is accepted H0 is rejected. So, it can be concluded that there is an influence on the implementation of the Independent Curriculum learning on the interest in learning PPKn in class IV SD Gugus Tomohon Selatan